Effect of the organic sulfur source on the photocatalytic activity of CdS. Issue 18 (11th April 2022) - Zhu, Qiong; Wang, Jinhua; Chen, Si; Fu, Hongquan; Zhang, Juan; Gao, Hejun; Liao, Yunwen
Abstract : By controlling the species of the organic sulfur source, CdS samples were produced with different photocatalytic performances by a low-temperature solvothermal method. Abstract : By controlling the species of the organic sulfur source, CdS samples were produced with different photocatalytic performances by a low-temperature solvothermal method. Different species of the organic sulfur source were chosen as the coordination agent to control the interactions in the crystal growth process. Among them, thioacetamide was the best coordination agent. The hydrophobic chain could be good for reducing the resistance of charge transfer, and increasing the rate of surface charge transfer and the lifetime of the photoexcited electrons. Benefiting from the hydrophobic chain, CdS shows an excellent photocatalytic hydrogen evolution rate of 943.54 μmol h −1 g −1 and a rhodamine B photocatalytic degradation rate of 99.1% in 60 min, which is superior to the photocatalysis of pure CdS prepared by many other methods.